Mercury, selenium and stable isotopes in four small cetaceans from the Southeastern Brazilian coast: Influence of feeding strategy. (November 2016) - Baptista, Gilberto; Kehrig, Helena A.; Di Beneditto, Ana Paula M.; Hauser-Davis, Rachel A.; Almeida, Marcelo G.; Rezende, Carlos E.; Siciliano, Salvatore; de Moura, Jailson F.; Moreira, Isabel
Abstract: Dolphins are good bioindicators of the contamination status of marine ecosystems, since their dietary and habitat plasticity in both coastal and offshore ecotypes provide information on the trace elements levels originated from natural and anthropogenic sources. In this context, this study aimed to investigate provides mercury (Hg), selenium (Se) levels, trophic ecology and feeding environments of four small cetaceans ( Tursiops truncatus, Steno bredanensis, Sotalia guianensis and Pontoporia blainvillei ) inhabiting the central-northern coast of Rio de Janeiro State, southeastern Brazil. For the latter, δ 15 N and δ 13 C stable isotopes were used as indicators in this regard. Stable isotope values indicate that the four studied species have distinctive foraging habitats, coastal and least coastal, and occupy different trophic positions. The significant relationship found between muscle Hg and δ 15 N suggests that individual foraging preference remains relatively constant for the studied dolphin species over extended periods. The individual prey size and species are probably responsible for the differences found in Hg and Se concentrations in muscle tissue among all dolphin species. The vulnerable small coastal cetacean, P. blainvillei, which feeds on small teleost fish and squid, presented the lowest muscular Hg concentrations (less than 3.5 μg g −1  dry wt.). Meanwhile, S. bredanensis is more likely to uptake large amounts of trace elements among the four dolphin species, due to its feeding habits mainly being large offshore fish that accumulate high amounts of trace elements in organs and tissues. Differences found between Hg concentrations in fetus-mother pairs were much higher in S. guianensis than in P. blainvillei, suggesting that maternal contribution of Hg via placenta was more significant for the former. Graphical abstract: Highlights: δ 15 N values indicate that the dolphin species occupy different trophic positions. δ 13 C values indicate that S. bredanensis is the least coastal of the four dolphins. The most vulnerable dolphin, P. blainvillei, showed the lowest Hg levels. Hg and δ 15 N relation indicates relatively constant foraging habitats for dolphins. Abstract : Differences in Hg and Se levels are due to dolphin prey size and species, while stable isotope values indicate distinctive foraging habitats and trophic positions.